A CORRELATIONAL-COMPARATIVE STUDY OF GRADE 4, GRADE 5, AND GRADE 6 STUDENTS’ SELF-EFFICACY FOR LEARNING AND PERFORMANCE IN INTEGRATED SUBJECTS WITH THEIR ACADEMIC ACHIEVEMENT IN A MOTHER TONGUE-BASED MULTILINGUAL EDUCATION CONTEXT IN 5 SJN-CBE SCHOOLS IN - JA HTOI DIN; LYNCH, RICHARD (Scholar: Human Sciences, 2022)
The purpose of this quantitative study was to investigate whether there was a significant relationship between self-efficacy for learning and performance in integrated subjects of Grade 4, Grade 5, and Grade 6 students and their academic achievement in 5 SJN-CBE Schools, Northern State, Myanmar. An adapted version of the Motivated Strategies for Learning Questionnaire by Pintrich, Smith, Gracia, and McKeachie (1991) was used to collect data from a total of 433 students; 117 Grade 4 students, 159 Grade 5 students, and 157 Grade 6 students. The subjects' final assessment results were used to determine the integrated subjects' academic achievement levels. The researcher also compared the self-efficacy for learning and performance in integrated subjects among Grade 4, Grade 5, and Grade 6 students. Descriptive statistics (means and standard deviations) and statistical hypothesis testing (correlational analysis using Pearson product-moment correlation and one-way ANOVA) were used to analyze the data. The research findings indicated high levels of self-efficacy for learning and performance in integrated subjects of Grade 4, Grade 5, and Grade 6. The integrated subject's final assessment result revealed that grade 4, Grade 5, and Grade 6 students had good academic achievement. Pearson product-moment correlation suggested that self-efficacy for learning and performance in integrated subjects of Grade 5 and grade 6 students and their academic achievement were significantly positively correlated; in contrast, there was no significant relationship between students' self-efficacy for learning and performance in integrated subjects of Grade 4 students and their academic achievement. The findings indicated a significant 1 M.Ed. in Curriculum & Instruction, Principal, Church-Based Education Shan State Kachin Baptist Union, Loihkang Road, Kawnghka, Kutkai, Northern Shan State, Myanmar. jarhtoidin5@gmail.com 2 Ph.D., Assistant Professor, Graduate School of Human Sciences, Assumption University, Thailand. richardlynch2002@yahoo.com 187 Scholar: Human Sciences, ISSN 2586-9388, Vol.14 No.2 (Jul.-Dec. 2022) difference in self-efficacy for learning and performance in integrated subjects between Grade 4 and Grade 5. Still, there was no significant difference between Grade 4 and Grade 6 students and between Grade 5 and Grade 6 students. Recommendations for students, teachers, parents, implementers and administrators of SJN-CBE, and future researchers are provided.